Discourse features of vendor-customer interaction in a transactional setting in Sibu - Lau, Kimberley Yih Long (Universiti Malaysia Sarawak (UNIMAS), 2012)
The study examined the discourse features of vendor-customer interaction in a transactional setting in Malaysia. The study focused on the schematic structures of transactions in the retail encounter and the languages used for various stages of the encounter. A total of 100 naturally-occurring interactions between vendors and customers in a traditional Chinese cake shop in Sibu were audio recorded for analysis. Relevant contextual infonnation and non-verbal expression of the vendors and customers were observed and noted. Semi-structured interviews were conducted with the sellers to obtain their perspectives of the transactions. Fourteen transactions in three cake shops of the same type were recorded and analysed to verify the discourse features of the retail encounter in this study. The results indicated that the cake shop transactions were realised in eight functional stages, namely, Sale Request, Sale Enquiry, Sale Initiation, Greeting, Sale Compliance, Goods Handover, Purchase and Purchase Closure. Among the eight stages, four of the stages (Sale Request, Sale Compliance, Purchase and Goods Handover) were obligatory stages of the retail encounter, with Sale Request, Purchase and Goods Handover stages being realised non-verbally. Stages which functioned as greetings and closings were infrequently present in the retail encounter of the present study. All the stages of this study were not restricted by any specific sequences. The results also showed that the language choice for interaction depended on the ethnicity of the customers, in which Mandarin and Chinese vernacular languages (Foochow, Hokkien) were used for intra-ethnic communication whereas Bahasa Metayu and Bazaar Malay were used for inter-ethnic communication. The language choice for ,transaction in this study was detennined by the customers and the sellers accommodated to the choice by code switching. Switching in the content words related to price, type, quantity, turn, availability and appreciation indicated the importance of such words in transactional interaction, and pointed to the stages of Sale Enquiry, Sale Request and Purchase Closure being enacted in a language which was different from the language of the interaction. The findings have implications for designing marketing plans.